Perfil epidemiológico del embarazo en adolescentes en el Hospital Amazónico de Yarinacocha, Ucayali - periodo 2010 - Fernández Tuesta, César (2012)
He performed this study in order to determine the epidemiological profile of teenage pregnancy in the hospital Yarinacocha Amazon, Ucayali-period 201O, the sample consisted of 979 pregnant adolescents attended during the study year, which constituted 100% of the accessible population, reported by the registration of perinatal information system (SIP2000). Quantitative approach was used, not experimental, descriptive, simple, and data were analyzed using the SPSS v20 and Microsoft Excel 2010. The specific objectives addressed were to determine the epidemiological factors in teenage pregnancy, obstetric factors associated with pre-existing conditions and present and more common in pregnant adolescents, arriving to the following conclusions: the average age of pregnant adolescents was 17.1 years of 24.8% single marital status, level Of education of incomplete secondary 50.3%, occupying 88.0% housewives, 21.7% without antenatal care. Obstetric factors that increase the presence of diseases in the pregnant teenager ended by caesarean section 14.6%, 41.6% had anemia and 17.1 % declare that 1 have had at least one abortion. The preexisting conditions present in the pregnant adolescents were hypertensive disorders 3.2% and 25.3% urinary tract infection. Maternal mortality in adolescent pregnancy in the Amazonian Yarinacocha Hospital was a case in 2010, representing a rate of 10 x 100 000 NV